2020
DOI: 10.1115/1.4045209
|View full text |Cite
|
Sign up to set email alerts
|

An OpenFOAM-Based Extension of Low-Re k–ε Model to the Partially Averaged Navier–Stokes Methodology for Simulating Separated Flows With Heat Transfer

Abstract: The partially averaged Navier–Stokes (PANS) methodology is known to give improved performance over the traditional Reynolds-averaged Navier–Stokes (RANS) formulation at an affordable computational cost. Over the years, PANS has gained popularity in both industry and academia. In this work, we strive to improve the performance of the k–ε-based PANS methodology by formulating a low-Reynolds-number (LRN) k–ε model-based PANS closure. We have compared the PANS closure based on Launder-Sharma k–ε model (LSKE) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Liu et al 11 implemented the RNG k - ϵ model (instead of the simple linear Boussinesq eddy viscosity model) and demonstrated improved predictions over an aerofoil and in a flow through a centrifugal pump. Recently, Chakraborty et al 12 performed a detailed comparative study of three prominent wall-resolving models within the k − ϵ framework (the Launder Sharma k − ϵ model, 13 the two-layer k − ϵ (TLKE) model of Chen and Patel 14 and the Lam–Bremhorst model 15 ) and demonstrated that despite the more frequent use of the TLKE model in conjugation with PANS in the previous studies, it is the Launder–Sharma k − ϵ model which shows significantly improved predictions of hydrodynamics as well as the heat transfer coefficients in flows past bluff bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 11 implemented the RNG k - ϵ model (instead of the simple linear Boussinesq eddy viscosity model) and demonstrated improved predictions over an aerofoil and in a flow through a centrifugal pump. Recently, Chakraborty et al 12 performed a detailed comparative study of three prominent wall-resolving models within the k − ϵ framework (the Launder Sharma k − ϵ model, 13 the two-layer k − ϵ (TLKE) model of Chen and Patel 14 and the Lam–Bremhorst model 15 ) and demonstrated that despite the more frequent use of the TLKE model in conjugation with PANS in the previous studies, it is the Launder–Sharma k − ϵ model which shows significantly improved predictions of hydrodynamics as well as the heat transfer coefficients in flows past bluff bodies.…”
Section: Introductionmentioning
confidence: 99%